Methotrexate Detection Based On The Optical Properties Of Carbon Nanotubes And Silver Nano Particles Nanocomposites - Fida Mohammad Mohammadi (Aksara: Jurnal Ilmu Pendidikan Nonformal, 2021)
In this experiment, glassy carbon electrode with multi walled carbon nanotubesnanocomposites have been prepared in different concentration in order to see ifmethotrexate is anticancer drug. For the purpose of characterizing the structures,nanocomposites were analyzed by scanning electron microscope. Optical measurements of different concentrations were conducted by z-scan method and the results show that by rising the concentration, nonlinear refractive index and linear absorption coefficient increases. The values of nonlinear refractive index are in orders of ????????−???? ???????????? ????.